Rancang Bangun Aplikasi Pengenalan Satwa dengan Metode Incremental Berbasis Android di Taman Safari Indonesia - Adinda Nurkhalifah Akbal; Niki Ratama; Rachmat Julianto; Sevhia Khoirun Nisa (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
Along with the rapid development of technology and information, information systems have a very important role for an organization or company The Android-based incremental method of animal recognition education application at Taman Safari Indonesia is an innovative solution to improve the experience of tourists in learning and getting to know various types of animals in Taman Safari Indonesia. This application is designed as an interactive learning tool that utilizes mobile technology to provide complete and interesting information about the animals in the safari park. Incremental methods are used in the development of these applications to provide users with a gradual learning experience. The main advantage of this app is that it gives you quick and easy access to information about the animals in Taman Safari Indonesia. With this application, tourists can optimize their visit time and get a more interactive and fun learning experience. In research on the use of this application, a trial was conducted on a group of Indonesian Safari Park tourists. The evaluation results show that this application has succeeded in increasing user knowledge and interest in the animals in the safari park. This application is expected to be an effective tool in environmental education and wildlife conservation in Indonesia.